Pharmacognostical Analysis and Preliminary Studies of the Chemical Constituents from the Roots of Senna alata Linn. - K, Husain; J.A, Jamal; Safran N.A, Abu; N.H, Ahmad; J, Jalil; I, Jantan; J, Latif; U, Suki, (Malaysian Journal of Science, 2005)
Senna alata L. (syn. Cassia alata L.) belongs to the family Leguminosae and is locally known as either Gelenggang Besar, Daun Kurap or Ludanggan. The leaves are traditionally used for the treatment of skin diseases such as ringworm and pityriasis versicolor. In this study, a pharmacognostical analysis was performed on the roots of S. alata using methods described by the Malaysian Herbal Monograph [1]. Powdered S. alata root was dark brown with bitter taste and mild odour; contained microscopical features such as fibres, vessels with spiral and bordered pit thickening, twinned-prism and prism calcium oxalate crystals, parenchymal cells, cork cells and starch cells; and produced distinct colour when reacted with different chemical reagents. A reasonable thin-layer chromatographic profile was obtained using pre-coated silica gel GF₂₅₄, mobile phase chloroform-methanol (9:1), and then detected under daylight after treatment with Anisaidehyde/H₂SO₄ reagent. The extractive values of powdered root for cold ethanol-soluble, cold water-soluble and hot water-soluble methods were obtained as 1.77%, 1.41 % and 1.77% respectively. Determination of moisture content by loss on drying method was 9.37%. In addition, a phytochemical study carried out on the ethyl acetate extract of S. alata root resulted in the isolation of two compounds, that is, a steroidal compound, stigmasterol, and emodin (1,6,8-trihydroxy-3-methylanthraquinone), which is a common compound of Senna species. The structures were elucidated using spectroscopic techniques (¹H-NMR, ¹³C-NMR and MS) and by comparison with the literature data.